Antigen-Specific B Memory Cell Responses to Plasmodium falciparum Malaria Antigens and Schistosoma haematobium Antigens in Co-Infected Malian Children - Lyke, Kirsten E. (Public Library of Science, 2012)
Polyparasitism is common in the developing world. We have previously demonstrated that schistosomiasis-positive (SP) Malian children have age-dependent protection from malaria compared to matched schistosomiasis-negative (SN) children. Evidence of durable immunologic memory to malaria antigens is conflicting, particularly in young children and the effect of concomitant schistomiasis upon acquisition of memory is unknown. We examined antigen-specific B memory cell (MBC) frequencies (expressed as percentage of total number of IgG-secreting cells) in 84 Malian children aged 4–14 to malaria blood-stage antigens, apical membrane antigen 1 (AMA-1) and merozoite surface protein 1 (MSP-1) and to schistosomal antigens, Soluble Worm Antigenic Preparation (SWAP) and Schistosoma Egg Antigen (SEA), at a time point during the malaria transmission season and a follow-up dry season visit. We demonstrate, for the first time, MBC responses to S. haematobium antigens in Malian children with urinary egg excretion and provide evidence of seasonal acquisition of immunologic memory, age-associated differences in MBC acquisition, and correlation with circulating S. haematobium antibody. Moreover, the presence of a parasitic co-infection resulted in older children, aged 9–14 years, with underlying S. haematobium infection having significantly more MBC response to malaria antigens (AMA1 and MSP1) than their age-matched SN counterparts. We conclude that detectable MBC response can be measured against both malaria and schistosomal antigens and that the presence of S. haematobium may be associated with enhanced MBC induction in an age-specific manner.